2016
DOI: 10.1108/er-06-2015-0110
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the HRM-performance relationship: the role of creativity climate and strategy

Abstract: Exploring the HRM-performance relationship: the role of creativity climate and strategy Purpose While an established stream of research evidence has demonstrated that Human Resource Management (HRM) is positively related to organisational performance, explanations of this relationship remain underdeveloped while performance has been considered in a narrow fashion. Exploring the relevant but often neglected impact of creativity climate, this paper examines key processes (mediation and moderation) linking high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 130 publications
(256 reference statements)
0
70
0
1
Order By: Relevance
“…Second, this study explores the mediating role of creativity climate; our findings show that creativity climate mediates the link between EIP and green product innovation performance. The existing studies have suggested that high performance work systems are positively and significantly related to creativity climate, which contributes to organizational performance (Heffernan et al, ). Other research has focused on the outcomes of creativity climate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, this study explores the mediating role of creativity climate; our findings show that creativity climate mediates the link between EIP and green product innovation performance. The existing studies have suggested that high performance work systems are positively and significantly related to creativity climate, which contributes to organizational performance (Heffernan et al, ). Other research has focused on the outcomes of creativity climate.…”
Section: Discussionmentioning
confidence: 99%
“…Prior researchers have found that fostering a creativity climate contributes to firms both the individual and organizational levels (Ghosh, ; Woodman, Sawyer, & Griffin, ). A climate that is conducive to creativity is characterized by the formal and informal practices that guide and inform supportive, self‐initiated, and persistent ways to work, which can support the development and execution of new and novel ideas, which in turn enhance organizational creativity and innovation (Baer & Frese, ; Heffernan, Harney, Cafferkey, & Dundon, ). Following this logic, we propose that creativity climate positively influences green creativity.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…As a research context, Ireland is relatively unique in lacking a substantive body of research exploring people management issues at national level (for notable exceptions see Heffernan, Harney, Cafferkey, and Dundon 2016;Guthrie, Flood, Liu, and MacCurtain 2009). In particular, there is an identified deficit of sector specific studies incorporating multilevel respondents (Cafferkey and Dundon 2015).…”
Section: The Research Contextmentioning
confidence: 99%
“…According to Yström, Aspenberg, & Kumlin, (2015) climate for creativity play a central role in motivating the workforce to think creatively. Creativity supporting climate consist of policies, practices, procedures, routines, and rewards that support creative ideas (Heffernan, Harney, Cafferkey, & Dundon, 2016). As mentioned by Mafabi, Munene, Ahiauzu, Mafabi, & Munene,(2015), the climate for creativity mainly characterized by recognition and reward for creative work and fair evaluation of creative work.…”
Section: Climate For Creativity and Employee's Creative Performance Bmentioning
confidence: 99%